2022
DOI: 10.3390/ijerph191610292
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Aspects of Climate Change Adaptation in Three Cities: A Qualitative Study

Abstract: Climate change presents an unprecedented public health challenge as it has a great impact on population health outcomes across the global population. The key to addressing these health challenges is adaptation carried out in cities through collaboration between institutions, including public health ones. Through semi-structured interviews (n = 16), this study investigated experiences and perceptions of what public health aspects are considered by urban and public health planners and researchers when planning c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Considering the range of potentially relevant documents for the inquiry of urban health, from newspaper articles to planning documents and official reports from local and central governmental agencies and other organisations, this method may be valuable for urban health researchers. For example, Macassa and others [ 90 ] have interviewed key stakeholders and analyzed official local climate change adaptation plans to understand how different coastal cities accommodate public health concerns in local adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the range of potentially relevant documents for the inquiry of urban health, from newspaper articles to planning documents and official reports from local and central governmental agencies and other organisations, this method may be valuable for urban health researchers. For example, Macassa and others [ 90 ] have interviewed key stakeholders and analyzed official local climate change adaptation plans to understand how different coastal cities accommodate public health concerns in local adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…The Health in All Policies (HiAP) framework promoted by WHO is for public policies across sectors to collaborate and systematically account for the health implications of decisions in policy-making [ 124 ]. This enables other sectors to consider the impact their own work has on health, while breaking down silos in building partnerships to promote health, equity, and sustainability as well as increase government efficiency [ 125 ]. Several health risks are affected or even determined by policy decisions in sectors outside the health sector [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated an association between depression and airborne particulate matter not related to wildfires [ 66 , 67 , 68 ]. This suggests a focus on policies that target local sources of non-wildfire-related air pollution (regulation of industrial and vehicular emissions, expansion of accessible greenspace) and prevention of physical health impacts associated with all forms of air pollution [ 49 , 69 ].…”
Section: Discussionmentioning
confidence: 99%